Sustainable construction practice: A review of Change Orders (CO) in Construction Projects - Wan Abdullah Zawawi, Noor Amila (2010)
Change order is a common phenomenon in any project in Malaysian construction industry. A change order is work that is added to or deleted from the original scope of work of a contract, which alters the original contract amount or completion date. Regardless of its causes, change order often resulted in disputes and dissatisfactions among the parties involved, project delay and difficult to manage due to additional costs. The impacts affect all players in construction projects. The objective of this study is to determine the main causes, effects of change orders in construction and to recommend control measures to minimize the impact from change orders. Literature review and a questionnaire survey targeted at building construction projects in Malaysia have been used as a tool to carry out this study. In this study, the findings obtained from the questionnaire will be the overall result for this study. However, considering that this is a preliminary study, the results gained are from the literature review. A literature search is made through previous case studies and literature reviews to collect all available information on the causes, effects and controls of change orders. The similarities and the differences of cases from each construction projects are compared and concluded as the outcomes of this case study. At the end of this study, it is hoped that these findings will guide the efforts towards a sustainable practice in the construction industry in Malaysia. This paper also explores and provides some guidelines and actionable information which can be used to improve the construction process.